2017
DOI: 10.1080/13603116.2017.1390001
|View full text |Cite
|
Sign up to set email alerts
|

How common are inclusive educational practices among Finnish teachers?

Abstract: Several instructional strategies have been recommended for use in heterogeneous classrooms, but the frequency of their actual use has remained largely unknown. Therefore, an electronic survey was sent to Finnish comprehensive school teachers (N =2,276) in order to assess the prevalence of three selected inclusive strategies: co-teaching, group work and differentiation. The results showed that co-teaching was used by 42% and group work by 43% of the teachers at least on a weekly basis, while differentiation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
3
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 25 publications
4
56
3
17
Order By: Relevance
“…According to a study by Ekstam et al (2016), in which they investigated support practices in Swedish-speaking schools in Finland, flexible grouping and differentiation are a more common form of support than co-teaching. Similarly, other studies (e.g., Saloviita, 2018;Saloviita & Takala, 2010;Takala & Uusitalo-Malmivaara, 2012) have demonstrated that coteaching is rare, especially among classroom teachers and subject teachers in Finnish-speaking schools as well. This may be partly due to a lack of time for planning the lessons together (Takala et al, 2009).…”
Section: The Finnish Model Of Support For Learning and Schoolingmentioning
confidence: 66%
“…According to a study by Ekstam et al (2016), in which they investigated support practices in Swedish-speaking schools in Finland, flexible grouping and differentiation are a more common form of support than co-teaching. Similarly, other studies (e.g., Saloviita, 2018;Saloviita & Takala, 2010;Takala & Uusitalo-Malmivaara, 2012) have demonstrated that coteaching is rare, especially among classroom teachers and subject teachers in Finnish-speaking schools as well. This may be partly due to a lack of time for planning the lessons together (Takala et al, 2009).…”
Section: The Finnish Model Of Support For Learning and Schoolingmentioning
confidence: 66%
“…Järgnevalt vaadeldaksegi, millised on levinumad kaasamist toetavad õpetamise meetodid ja kontekstuaalsed tegurid. (Bešic et al, 2017;Saloviita, 2018). Õpet diferentseeritakse eri viisidel.…”
Section: Kaasava Hariduse Tähendus Ja Rakendamise Viisidunclassified
“…Kõiki õppijaid kaasavaks meetodiks peetakse eakaaslaste toetatud (peer-assisted) koosõppimist (European Agency …, 2003), kus õpilased toetavad üksteist õpiülesannete täitmisel. Koosõppimise üheks positiivseks mõjuks hinnatakse õpilaste vaheliste suhete paranemist ja erivajadustega õpilaste kõrvalejäämise riski vähendamist (Saloviita, 2018).…”
Section: Kaasamist Toetavad õPetamise Meetodid Ja Kontekstuaalsed Tegunclassified
See 1 more Smart Citation
“…With the passage of the Individuals with Disabilities Education Improvement Act (IDEIA), the 'least restrictive environment' (LRE) of the general education classroom has been positioned as the optimal learning space (O'Connor, Yasik, & Horner, 2016). This change means that the educational philosophy has moved towards inclusion, where teachers at all levels and content areas are required to interact and work with students with special needs on a regular basis (Saloviita, 2018;Turnbull, Turnbull, & Weymeyer , 2010;US Department of Education, 2012). This push for including students with disabilities in the general education classroom has been seen internationally as well, not only in the area of education, but also by organizations like the United Nations, the World Bank and Council of the European Union (Doulkeridou, et al, 2011;Miskovic & Curcic, 2016;Ozel, Zhagan, Nor, Daud, & Ali, 2017;Saloviita, 2018).…”
Section: Introductionmentioning
confidence: 99%